Pengembangan Program Student Time Management Education untuk Penguatan Disiplin dan Kemandirian Belajar Peserta Didik Baru pada Masa Pengenalan Lingkungan Sekolah di SMAIT Ar-Rasyidiyah, Kecamatan Batang Tuaka, Riau - Fahrina Yustiasari Liriwati; Muhammad Ilyas; Mukhlizar Mukhlizar; Rika Ariyani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The transition of students from the previous level of education to the high school environment is an important phase that requires academic, psychological, and learning character readiness. One of the challenges that often arise in new students is the low ability to manage time, determine learning priorities, and build discipline and independence in the learning process. These problems are the basis for implementing a community service program through the Development of the Student Time Management Education Program as a Model for Strengthening Discipline and Learning Independence for New Students during the Introduction to the School Environment at SMAIT Ar-Rasyidiyah, Batang Tuaka District. This program aims to improve the understanding and skills of new students in managing time effectively as a strategy to build a disciplined and independent learning culture. The method of implementing the activity uses an educational-participatory approach through the stages of identifying needs, preparing materials, implementing training, mentoring, and program evaluation. The activity material includes the concept of time management, preparing priority scales, planning daily activities, strategies to avoid academic procrastination, and the formation of independent learning habits based on the value of responsibility. The expected result of this activity is the formation of a time management education model for new students that can be applied sustainably in the school environment. This program is expected to raise students' awareness of the importance of time management, strengthen their academic discipline, and encourage independent learning to meet the demands of high school education. In addition to providing direct benefits to students, this program also serves as a strategy to strengthen school culture, fostering a generation of responsible, productive learners who are prepared to face the challenges of modern education.